Local Wisdom in the Ritual of Phanjolmamod of Meaung District, Surin Province - et. al., Phrakhrusrisunthonsarakit, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purposes of this research were 1) to study the concept and evolution of Phanjolmamod of Meaung district, Surin province, 2) to analytical study the belief and value in ethical dimension as reflected from Phanjolmamod ritual, and 3) to analyze the body of knowledge in ethical value. This work is qualitative research. Documentary studies and in-depth interviews were used, and empirical analysis. The result indicated that this ritual's concept and evolution were caused by a mixed belief of Buddhism, Brahminism, and original beliefs such as ghosts, spirits, natural phenomena, and mystery beliefs that are not verified. The evolution of this ceremony does not indicate the time. It can be divided into two periods, namely: the traditional period, which the characteristics of strict ritual practices, but modern times are characterized by unstrung practices, and the number of believers in this ritual has a reduced effect. The beliefs and ethical values expressed through the Phanjolmamod are characteristics of the mixed beliefs of the Buddhist beliefs of Karma, Brahmin’s beliefs in the form of rituals and ghosts, and spirits that appear naturally, mystifications that look after the descendants. The ethical values that appear include: moral values, planning values in life, goals and achievements of life, ethical values of coexistence in society, and values in the Buddhist dimension are understanding and realizing the reality of life. The body of knowledge that is instructed people to practice the five precepts, gratitude, believing the karma, and welfare of people in society for peaceful coexistence..